Exploring the Role of Immunotherapy in Cancer Treatment: A Systematic Review - Abdirasulova, Abdirasulova Zhainagul; Shaker, Alhamza Abdulsatar; Kadhim, Mustafa Egla; Al-Marayaty, Shatha Sadiq; Brieg, Jassim Mohamed; Siddiqui, Mohd Faizan (Trends in Immunotherapy, 2025)
In recent decades, immunotherapy has revolutionized the landscape of cancer treatment, offering novel therapeutic approaches that harness the body's immune system to combat malignancies effectively. This systematic review explores the pivotal role of immunotherapy in oncology, highlighting its diverse modalities, mechanisms of action, clinical applications, and ongoing challenges. Beginning with an overview of the historical evolution of cancer therapy, emphasis is placed on the emergence of immunotherapy as a cornerstone alongside traditional modalities such as chemotherapy and surgery. The review comprehensively examines various types of immunotherapy, including checkpoint inhibitors, chimeric antigen receptor T cells (CAR T cells) therapy, cytokine therapy, oncolytic viruses, and exosome-based therapies. Mechanisms behind these treatments are clarified, showing how they boost anti-tumor immune system reactions and thus enhance patient outcomes. Recent advancements for each modality are discussed, drawing on seminal studies and clinical trials cited in the literature. Furthermore, the review addresses clinical successes and challenges associated with immunotherapy, including resistance mechanisms and adverse effects, as highlighted in recent research. Technological innovations in drug delivery systems and biotechnology are explored as critical enablers of immunotherapy's efficacy and safety profiles. Finally, the review outlines future directions in the field, proposing strategies to overcome current limitations and optimize treatment efficacy. The synthesis of findings underscores the transformative impact of immunotherapy on cancer care and highlights opportunities for further research and clinical integration.